Determinants of malnutrition among urban slum children in Bangladesh - Fakir, Adnan M S; Khan, M. Wasiqur Rahman (© 2016 Health Economics Review, 2016)
This article was published in Health Economics Review [©2015 Fakir and Khan] and the definite version is available at: http://healtheconomicsreview.springeropen.com/articles/10.1186/s13561-015-0059-1 The article website is at: http://healtheconomicsreview.springeropen.com/